An improved gain and directivity design of an antipodal Vivaldi antenna for ultra‐wideband detection - Wang, Jingjing; Li, Yongcheng; Liu, Jianwei; Fan, Yucheng; Hou, Kangming; Xu, Huaqiang (Microwave and optical technology letters, 2024)
A novel antipodal Vivaldi antenna (AVA) is proposed to achieve improved gain and directivity. To enhance the bandwidth of the antenna, a series of equal‐sized slots are etched onto the patch surface. Additionally, a dielectric lens with a fan‐shaped structure is integrated along the patch openings to boost gain. The length of the lens which will affect the radiation characteristics of the antenna in the end‐fire direction will be discussed. Furthermore, three arrays of directors are added to enhance the directivity. The fabricated antenna is then measured using a vector network analyzer in a microwave chamber to assess its performance. The results indicate that the antenna's minimum operating frequency is reduced by 0.5 GHz after etching the slots. Besides, the average gain is improved by 1 dBi after installing the fan‐shaped expansion structure. By introducing the directors, the sidelobe levels decrease and the 3 dB Half‐Power Beamwidth becomes sharper. Finally, an ultra‐wideband (UWB) detection experiment is designed to analyze the detection capability of the fabricated antennas. The results demonstrate that the antenna is well‐suited for UWB applications.